2019
DOI: 10.1002/jobm.201900353
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of esterase and lipase producing haloalkaliphilic bacteria from Lake Magadi in Kenya

Abstract: Lipids are hydrocarbons comprised of long‐chain fatty acids and are found in all living things. In the environment, microorganisms degrade them to obtain energy using esterases and lipases. These enzymes are nowadays used in different industrial applications. We report isolation of 24 bacteria with esteresic and lipolytic activity from Lake Magadi, Kenya. The isolates were characterised using morphological, biochemical, and molecular methods. Isolates grew at an optimum salt concentration of 5–8% (w/v), pH ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Total microbial community DNA was isolated using the phenol-chloroform protocol as described [20]. Obtained DNA pellets were air-dried and resuspended in 30.0 µl of PCR water.…”
Section: Dna Isolation Amplicon Library Preparation and Sequencingmentioning
confidence: 99%
See 1 more Smart Citation
“…Total microbial community DNA was isolated using the phenol-chloroform protocol as described [20]. Obtained DNA pellets were air-dried and resuspended in 30.0 µl of PCR water.…”
Section: Dna Isolation Amplicon Library Preparation and Sequencingmentioning
confidence: 99%
“…Cells for nucleic acid extraction were harvested by centrifuging 1 ml of the broth cultures. Bacterial genomic DNA was isolated using the phenol-chloroform protocol as described [20]. The 16S rRNA gene was amplified using bacterial universal primers pair 8F (5′-AG (A/G) GTT TGA TCC TGG CT-3′) and 1492R reverse, (5′-CGG CTA CCT TGT TAC GAC TT-3′) on a Sure cycler 8800 (Agilent Technologies).…”
Section: Identification Of Bacterial Isolatesmentioning
confidence: 99%
“…Strain LMS39 was isolated from dry sediments of Lake Magadi, Kenya (1°43′–2°00′S, 36°13′–36°18′E). Sediment (0.1 g) was serially diluted, and 10 −9 and 10 −10 dilutions were spread onto basal agar medium containing peptone (2 g/L), yeast extract (0.5 g/L), K 2 HPO 4 (1 g/L), CaCl 2 ·2H 2 O (0.05 g/L), MgSO 4 ·7H 2 O (0.1 g/L), and agar (14 g/L) ( 3 ). The medium was prepared with sterile lake water and supplemented with 1% (wt/vol) cellulose.…”
Section: Announcementmentioning
confidence: 99%
“…Edwin et al (2019) recovered 11 isolates affiliated with the cyanobacterial orders Chroococcales, Oscillatoriales, Pleurocapsales, and Nostocales. Recent studies have reported isolates affiliated with the genus Bacillus, Alkalibacterium, Staphylococcus, Micrococcus, Halomonas, and Alkalilimnicola (Kiplimo et al, 2019;Kipnyargis et al, 2022). Orwa et al (2020) recovered several fungal isolates affiliated with 18 different genera with Aspergillus, Penicillium, Cladosporium, Phorma, and Acremonium being dominant.…”
Section: Introductionmentioning
confidence: 98%